Modernist and Fundamentalist Debates in Islam
XI, 382 p.
Keywords: With resurgent interest in the Muslim world and in particular political Islam, this collection of translated essays by major Muslim thinkers from the Middle East and South Asia demonstrates the ongoing and contentious debate between modernizers seeking to adapt Western ways and fundamentalists who rejected them. From Jamal al-Din al-Afghani in the nineteenth-century to Ayatollah Khomeini in the twentieth, the selections provide an opportunity to examine a diversity of Muslim thinkers thoughts on important topics like jurisprudence, politics, relations with the west, and women in their own words.